TRANSFORMASI MEDIA PEMBELAJARAN DIGITAL DALAM PEMBELAJARAN BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - Mardhiyah Indah Sulistiyani, Inayatul; Hardoyono, Fajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The transformation of digital learning media has emerged as a central focus in Indonesia’s educational landscape, particularly at the elementary school level. This study aims to examine the implementation of digital learning media grounded in local wisdom as a strategic effort to enhance learning effectiveness. A qualitative research design was employed, utilizing data collection techniques such as interviews, observations, and document analysis in selected elementary schools that integrate local wisdom into their instructional practices. The findings reveal that the use of digital media incorporating elements of local wisdom not only increases students’ interest and motivation but also contributes significantly to strengthening their cultural identity. Furthermore, the data indicate that 75% of students reported higher levels of engagement when digital learning media were used effectively in the classroom. The study also highlights that teachers who have received adequate training in the use of digital technologies demonstrate greater proficiency in adapting instructional materials to reflect local cultural values. Overall, the transformation of digital learning media is expected to serve as a promising approach for improving the quality of elementary education while simultaneously preserving local wisdom in the face of rapid globalization.